Indicators of Innovation in the Strategic Management of the Textile Sector - Carreño, Franyelit Suárez-; Romero, Luis Rosales-; Naranjo, Christian Leonardo Chimbo-; Macias, Tatiana Elizabeth Cobeña-; Pico, Félix Vicente Zambrano-; Campuzano, Marcos Fernando Pazmiño- (International Journal of Membrane Science and Technology, 2023)
The internal structure of Ecuadorian textile companies includes an important aspect: their level of innovation. To remain competitive, it is crucial for these companies to continuously update and create cutting-edge processes that differentiate them from textile companies in other countries. This study examines the impact of innovation on the strategic management of the Ecuadorian textile industry. Data was collected through a survey based on a structured questionnaire, which was administered to textile company managers in the Sierra region. The questionnaire underwent validation by eight industry experts, and its high reliability was confirmed using Cronbach’s Alpha method. The results indicate a positive relationship between innovation and strategic management. Furthermore, the study identifies two key areas that offer significant opportunities for improvement in the short term: the selection and training of talented personnel and the integration of information and communication technologies (ICT) in management processes.